The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1248/jhs.49.337
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Jellyfish Toxin Study

Abstract: Recently, we have reported the chemical properties of some jellyfish proteinaceous toxins. These were the first chemical characterizations of jellyfish protein toxins to be reported. The isolation of the proteinaceous toxins in their active forms was the key step in the studies. We isolated the toxins from three box jellyfish (Cubozoa) species [Carybdea rastoni (C. rastoni), Carybdea alata (C. alata), and Chiropsalmus quadrigatus (C. quadrigatus)]. These toxins showed lethal toxicity to crustaceans and hemolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 9 publications
(8 reference statements)
1
32
0
4
Order By: Relevance
“…Although the rat studies suggest that Type I toxins elicit more potent cardiovascular effects in vertebrates than Type II toxins, some experimental evidence suggests that the Type II toxins elicit more potent effects in invertebrates. For example, in earlier studies on crustaceans, researchers found that the LD 50 values of Type II toxins CaTX-A and CrTX-A (5-25 g kg Ϫ1 ) were lower than the Type I toxin CqTX-A (80 g kg Ϫ1 ) (43). Comparative studies on the invertebrate toxicity of purified CfTX-1/2 and CfTX- A/B have yet to be published, but they would undoubtedly provide important information on the target specificity of the two toxin types.…”
Section: Discussionmentioning
confidence: 99%
“…Although the rat studies suggest that Type I toxins elicit more potent cardiovascular effects in vertebrates than Type II toxins, some experimental evidence suggests that the Type II toxins elicit more potent effects in invertebrates. For example, in earlier studies on crustaceans, researchers found that the LD 50 values of Type II toxins CaTX-A and CrTX-A (5-25 g kg Ϫ1 ) were lower than the Type I toxin CqTX-A (80 g kg Ϫ1 ) (43). Comparative studies on the invertebrate toxicity of purified CfTX-1/2 and CfTX- A/B have yet to be published, but they would undoubtedly provide important information on the target specificity of the two toxin types.…”
Section: Discussionmentioning
confidence: 99%
“…All three schypozoan jellyfishes had rather potent lethal toxicity compared with the two hydrozoans ( Table 1). Crustacean lethal polypeptide toxins isolated from box jellyfishes such as Carybdea rastoni [26], Carybdea alata [32], and Chiropsalmus quadrigatus [33] belong to a novel polypeptide family designated as the box jellyfish toxin family [16] and it may also be the case that a novel polypeptide toxin family could be present in the three coronate scyphozoan medusae. To date, some pharmaceuticals have been developed from marine natural toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Water-soluble extracts obtained from these deep-sea jellyfishes were subjected to (1) cytotoxicity, (2) hemolytic activity and (3) crustacean lethal toxicity tests. The crude extract preparation methods and bioactivity tests adopted in this study have been routinely used in our laboratory for discovering novel bioactive polypeptides from shallow-water cnidarians [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, Chiropsalmus and Chiropsella species are considered much less dangerous (but see Bengtson et al 1991). Differences in toxicity among chirodropids may be explained by differences in the amount of tentacle surface area, and consequently, the amount of venom that can be delivered (see Nagai 2003). Interestingly, an unvouchered tissue specimen from Palau appears to be closely related to C. yamaguchii from Japan, raising questions about the toxicity and identity of this chirodropid.…”
Section: Discussion (A) Phylogenetic Analyses and Signalmentioning
confidence: 99%
“…Similarly, lethal doses of venom appear much lower in C. brevipedalia when compared with Alatina sp. and C. yamaguchii (Nagai 2003). Note, however, that these haemolytic assays do not appear to have been standardized among treatments, potentially making direct comparisons unreliable.…”
Section: Discussion (A) Phylogenetic Analyses and Signalmentioning
confidence: 99%